A novel biomagnetic approach to study caecocolonic motility in humans - Romeiro, Fernando Gomes [UNESP] (2006)
Motility patterns play a major role in human colonic functions; however, its physiological significance is poorly understood. Several studies have been introducing the Alternating Current Biosusceptometry (ACB) as a valuable tool in gastroenterology and pharmaceutical research. Using gold standard techniques, great effort has been made to validate ACB as a method for measuring gastrointestinal motility in humans and animals. The aim of this study was to evaluate caecocolonic motility and its response to a meal in healthy volunteers. The results showed a dominant frequency of 3.17 +/- 0.13 cycles per minute (mean +/- SD) that remained unchanged even after a standardized meal (P > 0.01). The colonic response to a meal was recorded as a considerable increase in amplitude, reflected by motility index (P < 0.01) and was observed for all the volunteers. The caecocolonic motility could be assessed by the ACB providing new insights into physiological patterns of motility. Moreover, the method is non-invasive, radiation-free, cost-effective and independent of bowel preparation.